Mindfulness for the Mental Health of Working Women: How Effective Is It and What Are the Challenges? - Restiana Hapsari; Mufatihatul Nisa; Yulia Sukmawan; Ray Basrowi; Prihatini Novitasari (Universitas Muhammadiyah Surakarta, 2025)
The mental health of working women is a critical issue within the context of increasing dual burdens of work and domestic responsibilities. Mindfulness interventions have been proposed as an effective approach to enhancing psychological well-being. The objectives was to examine the effectiveness of mindfulness interventions on the mental health of working women, identify implementation challenges, and formulate recommendations for future research. This study is a systematic literature review (SLR) of 14 quantitative and qualitative studies published in indexed journals. Quality assessment was conducted using the JADAD Score, JBI Checklist, and MMAT according to the study design. Out of 2,400 articles identified through Scopus and Google Scholar databases, 14 articles met the inclusion criteria and were analyzed in this review. These studies employed various methodological designs, including RCTs (n=6), quasi-experimental (n=5), and observational or cross-sectional studies (n=3). Based on the assessment of effectiveness, mindfulness interventions were classified as highly effective (n=6), moderately effective (n=5), and less effective (n=3), depending on intervention protocol, intensity of participation, and institutional support. Structured protocol-based mindfulness interventions with facilitators (MBSR, MBCT, MAC) demonstrated the highest effectiveness compared to self-guided or trait-based interventions. The majority of studies indicated that protocol-based mindfulness interventions such as MBSR and MBCT effectively reduced stress, burnout, and anxiety, and enhanced self-compassion and psychological well-being. Main barriers included time constraints, participant retention, and methodological limitations. Mindfulness interventions are a promising strategy to support the mental health of working women.